Psychological Distress and Quality of Life among Head and Neck Cancer Patients after 3- and 6-Months Post-Treatment-A Hospital-Based Study - Mamatha E; Saka Saritha D; Mutthineni Durga Chowdary L; Bhushanam Darji Naga; Teji P Apoorva Venkata (Wolters Kluwer Medknow Publications, 2024)
IntroductionCancers affecting the parts of the head and neck significantly impact patients. Among head and neck cancer (HNC) patients, the visible signs and symptoms of the disease or the side effects of treatment modalities can cause various degrees of functional impairment such as mastication, swallowing, communication, and disfigurement. ObjectiveTo assess psychological distress and quality of life in head and neck cancer patients after 3 and 6 months' post-treatment. Materials and MethodsA hospital-based follow-up study was conducted among head and neck cancer patients who came for routine follow-up after treatment in five cancer hospitals in Hyderabad City. Patients were categorized based on the treatment into surgery, chemotherapy, radiotherapy, and combination of all and the same subjects were followed; after 3 months, psychological distress and quality of life were assessed by distress thermometer and functional assessment of cancer therapy head and neck (FACT H and N). ResultsA total of 235 participants were included in the study. Mean age was 58.2 ± 8.7 years. The mean scores of psychological distress at baseline were 4.6 ± 1.2, and after follow-up, it was 3.4 ± 1.2 and the mean scores of quality of life at baseline were 76.4 ± 15.6, and after follow-up, it was 75.5 ± 12.5. ConclusionThe mean scores of psychological distress had reduced from baseline to follow-up with negligible improvement in the quality of life.